2021
DOI: 10.1371/journal.pntd.0009957
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the unwillingness of Jordanians, Palestinians and Syrians to be vaccinated against COVID-19

Abstract: Background The COVID-19 pandemic is expected to continue to inflect immense burdens of morbidity and mortality, not to mention the sever disruption of societies and economies worldwide. One of the major challenges to managing COVID-19 pandemic is the negative attitudes towards vaccines and the uncertainty or unwillingness to receive vaccinations. We evaluated the predictors and factors behind the negative attitudes towards COVID-19 vaccines in 3 countries in the Middle East. Methods A cross-sectional, self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Specifically, many participants in our study shared a “wait and see” attitude towards the vaccine – preferring to defer receiving the vaccine until more long-term consequences are clarified – or a preference for natural immunity, which has previously been associated with a lower likelihood of getting the influenza vaccine. 41–43 Similar to results of other vaccine studies, 36 , 44 the weighing of perceived risks and benefits of vaccination was central to decision-making among sample participants. These findings highlighted the need for increasing awareness and knowledge of the serious risks of coronavirus, the direct prevention benefits of the vaccines, and the safety of the ingredients in the vaccines.…”
Section: Discussionmentioning
confidence: 78%
“…Specifically, many participants in our study shared a “wait and see” attitude towards the vaccine – preferring to defer receiving the vaccine until more long-term consequences are clarified – or a preference for natural immunity, which has previously been associated with a lower likelihood of getting the influenza vaccine. 41–43 Similar to results of other vaccine studies, 36 , 44 the weighing of perceived risks and benefits of vaccination was central to decision-making among sample participants. These findings highlighted the need for increasing awareness and knowledge of the serious risks of coronavirus, the direct prevention benefits of the vaccines, and the safety of the ingredients in the vaccines.…”
Section: Discussionmentioning
confidence: 78%
“…The highest prevalence of vaccine hesitancy in this study was found in Palestine territories. A study that evaluated factors behind the unwillingness to receive vaccinations in Palestine territories suggested two main reasons for this, lack of vaccine evaluation and the possible long-term side effects ( 40 ). Moreover, many individuals obtain vaccine-related information from social media platforms ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many individuals obtain vaccine-related information from social media platforms ( 41 ). Younger age and lower education were also predictors of vaccine hesitancy ( 40 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was also observed in a study performed in Saudi Arabia where the vaccine refusers indicated that their safety concerns would only be dissipated with more reported clinical studies [84]. These concerns have been related to belief in conspiracy theories [85] and the wait-and-see approach to assess possible long-term health risks [86].…”
Section: Discussionmentioning
confidence: 72%